FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KETEPATAN JADWAL IMUNISASI DI DESA DENANYAR KECAMATAN JOMBANG WILAYAH KERJA PUSKESMAS PULO LOR JOMBANG KABUPATEN JOMBANG: Factors Related To The Accuracy Of The Immunization Schedule In Denanyar Village, District Jombang Working Area Of Pulo Lor Health Center Jombang, Jombang District - Wijayanti, Arshi; Grah Prihartanti, Niken; Fitrah Ningtyas, Septi (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
The accuracy of the immunization schedule is very necessary. If it is not on schedule it can usually cause the dose to be reduced so that it can be a problem that the immune power of the vaccine is not optimal and the vaccine power and antibody levels will be lost or very low if the immunization is not on schedule. determined. This study used an analytic survey design with a cross-sectional approach. The population in this study were mothers who had children aged 9-24 months, the sample in this study were 20 people in the Posyandu Melati 2 Denanyar Village, the sampling technique was simple random sampling. Data collection using a questionnaire. Data analysis was univariate, bivariate using the chi-square test. The results showed that there was a relationship between knowledge and p-value (sig) = 0.005 <0.05, work with a p-value (sig) = 0.005 <0.05, family support with a p-value (sig) = 0.010 <0.05, staff support health with a p-value (sig) = 0.010 <0.05 with Completeness of Basic Immunization in Children Aged 9-24 months in the Posyandu Melati 2 area, Denanyar Village. The conclusion in this study is that there is a relationship between knowledge, work, family support, health worker support with the accuracy of the basic immunization schedule. It is suggested to all related parties to carry out and monitor programs to increase the knowledge of mothers and the community about the importance of the accuracy of the basic immunization schedule for infants routinely and according to schedule.